Psychometric Properties of WISC-IV Verbal Scales: A Study of Students in China Who Are Blind. (May 2021) - Chen, Xiaomeng; Lu, Minghui; Bu, Wenfeng; Wang, Li; Wang, Yuru; Xu, Yulin; Zhong, Mingbo
Introduction: Numerous studies have investigated the use of Wechsler tests on individuals with visual impairments. However, few studies have examined the utilization of the fourth edition of the Wechsler Intelligence Scale for Children (WISC-IV) for such individuals. This study investigated the reliability and validity of the WISC-IV Verbal Scales' (i.e., the Verbal Comprehension Index [VCI] and the Working Memory Index [WMI]) scores for children with blindness in China. Methods: One hundred children with blindness were assessed using the Chinese version of the WISC-IV Verbal and Nonverbal Cognitive Development Scales. Results: The results of this study generally support the internal consistency reliability and validity of WISC-IV Verbal Scale scores for Chinese children who are blind. The split-half reliability coefficients ranged from .79 to .97, while Cronbach's alpha or KR-20 (KR-20 is a measure of internal consistency reliability for measures with dichotomous choices) reliability coefficients ranged from .83 to .97. In terms of construct validity through exploratory factor analysis, the subtests of the WISC-IV Verbal Scale were confirmed to belong to VCI or the WMI as intended by the original structure of the WISC-IV. The convergent validity showed that the VCI and WMI scores were moderately and positively correlated with the Nonverbal Cognitive Development Scale. Discussion: The WISC-IV VCI and WMI were found to be valuable instruments for assessing the cognitive abilities of students in China with blindness. Finally, the limitations and significance of the study were also discussed. Implications for practitioners: The WISC-IV Verbal Scales may be used to assess the cognitive abilities of the numerous students in China who are blind and may be used as one of many tests to provide reference information for educational placement, educational planning, employment, and project evaluation.